2018
DOI: 10.1186/s13148-018-0452-9
|View full text |Cite
|
Sign up to set email alerts
|

Causal effect of smoking on DNA methylation in peripheral blood: a twin and family study

Abstract: BackgroundSmoking has been reported to be associated with peripheral blood DNA methylation, but the causal aspects of the association have rarely been investigated. We aimed to investigate the association and underlying causation between smoking and blood methylation.MethodsThe methylation profile of DNA from the peripheral blood, collected as dried blood spots stored on Guthrie cards, was measured for 479 Australian women including 66 monozygotic twin pairs, 66 dizygotic twin pairs, and 215 sisters of twins f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 55 publications
(77 reference statements)
5
53
0
Order By: Relevance
“…Since smoking is known to affect DNA methylation (Zeilinger et al, 2013), and participants with ADHD indicated to be smokers more often than healthy controls, we corrected for smoking in our model. A smoking score was calculated per individual, based on 177 CpG sites currently known to be differentially methylated by smoking (Zeilinger et al, 2013;Li et al, 2018). The average methylation effect of these CpG sites was calculated based on a discovery and replication cohort as previously described by Elliot and co-workers (Elliott et al, 2014).…”
Section: Assessment Of Smoking As Covariatementioning
confidence: 99%
“…Since smoking is known to affect DNA methylation (Zeilinger et al, 2013), and participants with ADHD indicated to be smokers more often than healthy controls, we corrected for smoking in our model. A smoking score was calculated per individual, based on 177 CpG sites currently known to be differentially methylated by smoking (Zeilinger et al, 2013;Li et al, 2018). The average methylation effect of these CpG sites was calculated based on a discovery and replication cohort as previously described by Elliot and co-workers (Elliott et al, 2014).…”
Section: Assessment Of Smoking As Covariatementioning
confidence: 99%
“…Results of that study confirmed numerous prior reports of associations between smoking and DNAm in several genes including, most notably, AHRR, F2RL3, and RARA. Because cross-sectional epidemiological studies do not permit inferences about whether DNAm associations are causes, consequences, or effects of third variables, Li et al (2018) used a genetically informative twin cohort to examine the heritability of the smoking-associated DNAm loci and found strong evidence that most of the observed epigenetic associations were attributable to the effects of cigarette use [22]. These findings are highly relevant to the epigenetics of PTSD because PTSD samples, especially from veteran cohorts, tend to have an elevated prevalence of cigarette smoking relative to the general population [23].…”
Section: Introductionmentioning
confidence: 99%
“…The epigenome is potentially malleable -changing with age and in response to a plethora of environmental and psychosocial factors [56], thus providing a mechanism mediating the interaction between genetic susceptibility and environmental risk exposures [57]. Given that environmental factors (such as smoking, stress and obesity) have been shown to both influence a person's epigenome [58][59][60] and accelerate the rate of telomere shortening [61,62] it is plausible that together these changes could influence the expression of subtelomeric genes.…”
Section: Epigenetic Regulation Of Telomere Lengthmentioning
confidence: 99%